2017
DOI: 10.1016/j.foodchem.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the key excreted molecule by Lactobacillus fermentum related to host iron absorption

Abstract: We have taken a vital step towards understanding why probiotic bacteria increase iron absorption in the gastrointestinal tract. We show here that Lactobacillus fermentum, one of the main probiotics of the microbiota, exhibits an extraordinary ferric-reducing activity. This activity is predominantly due to an excreted molecule: p-hydroxyphenyllactic acid (HPLA). Reduction of Fe(III) to Fe(II) is essential for iron absorption in the gastrointestinal tract. By reducing Fe(III), HPLA boosts Fe(II) absorption throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 22 publications
1
64
0
1
Order By: Relevance
“…The exact mechanism of this process is not well understood. Previous studies revealed that this inverse relationship can be probably due to increased iron absorption by the gut microflora . Moreover, Lactobacillus does not need iron for its development, so it can exist in iron‐deficient state .…”
Section: Human Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The exact mechanism of this process is not well understood. Previous studies revealed that this inverse relationship can be probably due to increased iron absorption by the gut microflora . Moreover, Lactobacillus does not need iron for its development, so it can exist in iron‐deficient state .…”
Section: Human Studiesmentioning
confidence: 99%
“…UA inhibits reactive oxygen species (ROS) production, and its increased synthesis positively influences the host's health state by protecting the host from oxidative stress and inflammation . Moreover, Lactobacillus fermentum present in the gut microflora, due to excreted p ‐hydroxyphenyllactic acid, shows a ferric‐reducing activity that enables the reduction of Fe(III) to Fe(II) . Fe(II), unlike Fe(III), can be absorbed by the host's enterocytes .…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 3 more Smart Citations